Comparing Serum and Salivary Levels of Vitamin D in Patients with Recurrent Aphthous Stomatitis and Healthy Individuals - Ayla Bahramian; Parisa Falsafi; Teymour Abbasi; Milad Ghanizadeh; Mehdi Abedini; Fatemeh Kavoosi; Maryam Koohsoltani; Fatemeh Noorbakhsh; Fatemeh Dabbaghi Tabriz; Shahin Rajaeih; Farzad Rezaei (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Recurrent aphthous stomatitis (RAS) is the most prevalent ulcerative condition of the oral mucosa. Many studies have emphasized on immunologic factors as the reason of inducing RAS; however, the exact etiologic cause of RAS has not been identified yet. Vitamin D has an endocrine function and regulatory effects on the immune system. It has potential therapeutic effects on autoimmune diseases, psoriasis, and neoplasms. Vitamin D deficiency has been detected in some autoimmune diseases such as rheumatoid arteritis. Purpose: The aim of the present study was to compare the serum and salivary levels of vitamin D in patients with RAS and healthy individuals. Materials and Method: In this cross sectional study, patients with RAS, referring to the Department of Oral Medicine, Tabriz Faculty of Dentistry, were evaluated after taking medical history, clinical examinations, and completing an informed consent form. The serum and salivary vitamin D levels were compared between case (n=26) and control (n=26) groups. Results: The mean serum vitamin D levels in the case and control groups were 33.0.7±12.41 and 50.89±9.30 (ng/dL), respectively, with a statistically significant difference (P<0.001). On the other hand, the mean salivary vitamin D levels in the case and control groups were 17.36± 8.01 and 20.79±6.31 (ng/dL), respectively, with no statistically significant difference (p= 0.09). In addition, the correlation between the serum and salivary levels of vitamin D was 56%, being statistically significant (p< 0.001). Conclusion: The serum levels of vitamin D in patients with RAS were significantly less than that in healthy individuals; however, there were no significant differences in salivary vitamin D levels between patients with RAS and healthy individuals. In addition, there was a significant and positive correlation between serum and salivary levels of vitamin D in all patients.